A New Approach to Modelling and Testing the Fatigue Strength of Helicopter Rotor Blades during Repair Process - Sałaciński Michał; Kowalski Rafał; Szmidt Michał; Augustyn Sławomir (Fatigue of Aircraft Structures, 2019)
The fatigue test was carried out on an element of a rotor blade removed from the Mi-2 helicopter. The purpose of the test was to check the fatigue strength of the repaired rotor blade. Metal composite rotor blades have a metal spar in the form of a box and the trailing sections in the form of metallic honeycomb sandwich panels. The trailing sections are bonded to the spar. The repair had been carried out at the point where the trailing section became debonded from the spar at the Air Force Institute of Technology in Warsaw using a methodology developed for carrying out repairs of rotor blades’ damage. All types of the Mi family helicopters are equipped with metal composite rotors blades. Depending on MTOW (Maximum Take-Off Weight) and destination of helicopters, blades differ in dimensions, but their design solutions are practically the same. For this reason, the developed repair methodology can be used for all characteristic rotor blades structures for Mi helicopters. The fatigue test was performed at the Łukasiewicz - Institute of Aviation in Warsaw, using a hydraulically driven fatigue machine. The fatigue test was carried out by performing over 1.1 million load cycles. In repair places, upon completion of fatigue testing, no damage was found.